ANALISIS PENGARUH PDRB PERKAPITA DAN ANGKA MELEK HURUF TERHADAP JUMLAH PENDUDUK MISKIN DI JAWA TENGAH PERIODE TAHUN 2015 & 2016 - Pipit Puspitasari (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
Poverty is a situation where an individual or a household has difficulty meeting basic needs. Poverty is also a social dilemma when social stratification forms levels and boundaries in society. As a result, there are deflections and limitations in relationships and communication between people at the top and bottom levels. This study aims to analyze the effect of GDP per capita and literacy rates on the number of poor people in Central Java in the 2015 and 2016 periods. This data analysis uses the panel data method using the Eviews 9 application and consists of the Chow Test (Likelihood Ratio), Hausman Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Partial Hypothesis Test (t test) & Simultaneous (F Test), Determination Value and Correlation.